Marketing Communication Strategy for Gold Installment Products to Increase the Number of Customers at Bank Syariah - Aminuddin, Luthfi Hadi; Wulandari, Samrotul Farida Agustina (Etihad: Journal of Islamic Banking and Finance, 2025)
Introduction: This study aims to analyze the marketing communication strategy of gold installment products in Islamic banking to increase the number of customers. Research Methods: The research method used is qualitative, with data collection techniques through in-depth interviews, observations, and document review. Results: The study results show that an effective marketing communication strategy combines traditional and digital media, sharia-based product education, and a personal approach that builds customer trust. The strategic advantages include compliance with sharia principles, product innovation relevant to market needs, responsive service, and consistent communication. These findings enrich the previous literature by providing empirical evidence that the success of gold installment products is determined by the attractiveness of gold investments and the effectiveness of marketing communication strategies that can build customer understanding and loyalty. Conclusion: This study recommends improving Islamic financial literacy, enhancing digital promotion, and building strategic partnerships to expand the market. These efforts are expected to make gold installment products competitive and sustainable Sharia investment instruments in the modern financial industry.